Synthesis and Antimicrobial Activity of Some 1, 3‐Disubstituted Indeno[1, 2‐c]pyrazoles. (31st October 2013) - Mohil, Rajni; Kumar, Devinder; Mor, Satbir
<x xml:space="preserve">Abstract</x> Synthesis of new 3‐alkyl indeno[1, 2‐c]pyrazoles, possessing 4‐substituted thiazole moiety at position‐1 derived from 2‐acyl indane‐1, 3‐diones, has been described. These compounds and their precursor were screened for their antibacterial (Staphylococcusaureus, Bacillus subtilis, Escherichia coli) and antifungal (Aspergillus niger, Candida albicans) activities.